Progress, prospect and challenges in glycerol purification process: A review - Ardi, M.S.; Aroua, M.K.; Hashim, Nur Awanis (Elsevier, 2015)
Glycerol surplus in recent decades due to global increase in biodiesel production has created a new form of challenge in terms of purification for crude glycerol. This review summarizes the progress of crude glycerol purification technologies using various techniques. Critical insights are given regarding the application of suitable techniques for crude glycerol purification which includes chemical pre-treatment, methanol removal, vacuum distillation, ion exchange, activated carbon and membrane separation technology. Extensive discussion is made in relation with stages and processes in the conventional, current and emerging glycerol purification technologies. Lastly, aspects concerning the challenges of glycerol utilization and purification are thoroughly discussed. (C) 2014 Elsevier Ltd. All rights reserved.